Level of Oral and Dental Health Knowledge In Adolescents Age 16-22 Years - Mardianti, Ferriza Tri; Rahma, Annisa; Ridho, Fiki Muhammad; Setyawan, Andika Putri; Santoso, Nabila Ulfa; Salma, Nadhifa; Ramadhani, Aulia (International Journal of Psychosocial Rehabilitation, 2020)
Dental and oral health are important because dental and oral health describes the overall health condition of the body. Poor dental health can cause a variety of dangerous disease complications. East Java Province is one of the provinces with a high prevalence of dental and oral health problems, which is 54.2%. The importance of knowledge of maintaining oral health should be applied by parents to children from an early age, thus after adolescence and adulthood later, children can take care of oral health properly. Objectives: To determine the level of dental and oral health knowledge in adolescents aged 16-22 years old in East Java. Methods: This study was a descriptive survey study using an online questionnaire form with a sample of adolescents aged 16-22 years old in East Java. Results: From this study found 175 respondents, the study results were presented in the form of a frequency table. There were 18 respondents with medium grades and 157 respondents get high scores. There were no respondents who get low marks. Conclusion: Adolescents aged 16-22 years old in East Java mostly have a high level of knowledge about oral health.